P791 Peripheral spondyloarthritis, peripheral arthritis, and IBD-related peripheral arthritis in patients with long-term IBD: Results from 20 years of follow-up in the IBSEN study. (16th January 2018) - Ossum, A; Palm, Ø; Cvancarova, M; Moum, B; Høivik, M; ,
Abstract: Background: Extraintestinal manifestations are common in patients with inflammatory bowel disease (IBD), and musculoskeletal manifestations are the most frequent. The aim of this study was to estimate the prevalence of peripheral spondyloarthritis and peripheral arthritis, including IBD-related arthritis in IBD patients 20 years after diagnosis, and to investigate potential associations with IBD severity. Methods: All patients with newly diagnosed IBD in four well-defined counties in southeastern Norway from 1990 to 1993 were included in the IBSEN study. The patients were followed for 20 years with regular follow-ups including clinical exams and questionnaires. The patients answered standardised questions regarding rheumatic symptoms and findings at the 5- and 20-year follow-ups. Peripheral spondyloarthritis was diagnosed according to the ASAS criteria and included patients with peripheral arthritis, dactylitis and/or enthesitis. Patients in whom other causes of peripheral arthritis (i.e. rheumatoid arthritis, reactive arthritis etc.) were ruled out, were defined as having IBD-related peripheral arthritis. Patients with and without peripheral spondyloarthritis and IBD-related peripheral arthritis were compared with regard to diagnosis, age, gender and variables indicative of IBD severity; disease location, extent, use of medication and patient-reported disease course. Crude comparisons were performed using the Chi-square test or Fisher's exact test when appropriate. Results: After 20 years, 599 (79.2 %) patients from the original cohort were alive and 441 (73.6 %) (296 UC and 145 CD) were evaluated. Throughout the disease course, peripheral spondyloarthritis had occurred in 123 patients (27.9 %). Peripheral arthritis, including those not related to IBD, had been diagnosed in 104 patients (24.0 %) and IBD-related peripheral arthritis had been present in 76 patients (17.2 %). No difference in the occurrence of these conditions between patients with UC and CD was found. The proportions of females were significantly higher ( p < 0.01) in the groups with peripheral spondyloarthritis (61.8 %) and IBD-related arthritis (67.1 %) compared with those without peripheral spondyloarthritis (46.4 %). There were no significant associations between IBD location, extent, medication use or patient-reported disease course in the groups with and without IBD-related peripheral arthritis or peripheral spondyloarthritis. Conclusions: The accumulated incidence of peripheral spondyloarthritis and IBD-related peripheral arthritis throughout 20 years of disease course was high, and were more common in females. IBD- severity did not differ between patients with and without the investigated rheumatic conditions.